Visitors' preferences on travel website content / Norfadhilah Mohd Akhuan, Fauzunnasirah Fazil and Shareenie Shera Abdul Hamid - Mohd Akhuan, Norfadhilah; Fazil, Fauzunnasirah; Abdul Hamid, Shareenie Shera (Research Management Institute (RMI), 2012)
This study is important to understand the preferences of visitors on travel website content. It is mainly confined to the features of travel websites that are preferred by visitors. This research is able to enhance the effectiveness of travel websites and increase the usability of travel websites among visitors. Besides that, this study also reveals the pattern of internet use among visitors when planning a trip and direction which lead them to perform online transaction. The three main objectives of the study are to: (1) define visitors' levels of usage of the travel websites as information source and for product purchase; (2) determine the website features that would most likely to attract and retain visitors; and (3) measure the relative importance of various content attributes on travel websites. The research method in this study involves a survey technique which will be used to gather information. A structured questionnaire will be distributed to the sample of study in Melaka tourist destination. The location for data collection is chosen based on the place where visitors could be accessed conveniently. Tourist destinations in Banda Hilir and Ayer Keroh have been seen as the appropriate location and the international and domestic visitors have been identified as the population for this study. The outcomes of this study will be used to indicate the existence of important features that could be considered in websites development. This study will present a comprehensive description on the preferences of visitors on travel websites content. This defines a mechanism which travel marketers could apply in developing travel websites that able to deliver effective and good service quality to visitors.